2023
DOI: 10.1021/acs.jpcc.3c04343
|View full text |Cite
|
Sign up to set email alerts
|

New Room-Temperature Ferroelectrics with Photoluminescent Properties

Wentao Zhang,
Shulin Jiao,
Min Zhao
et al.

Abstract: Organic−inorganic hybrid materials are highly versatile and can be easily modified, allowing for the deliberate construction of multifunctional ferroelectrics. In particular, the combination of photoluminescence and ferroelectricity in a single hybrid material holds great potential for various applications, such as lighting sensors, memory devices, and other multifunctional uses. In this study, we focused on 3-oxa-8-azabicyclo[3.2.1]octane hydrochloride (OAO) and designed two room-temperature ferroelectrics ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…STEs are transient defect species that emerge as a consequence of elastic lattice distortion by photoexcitation in a soft deformable lattice. Upon photoexcitation, free excitons are generated, which undergo self-trapping quickly due to the elastic lattice distortion stabilized by electron–phonon coupling in a low-dimensional compound with a soft liquid-like crystalline lattice. , Owing to the exciton self-trapping, the compound exhibits large Stokes shift, broad emission spectra, and long luminescence lifetime and is conducive for designing single-component white light LEDs. , Previously, several studies have demonstrated STE emission in hybrid manganese halides featuring Mn­(II) ions in tetrahedral coordination, showcasing red-emitting STE bands. Additionally, other reports have shown electron–phonon coupling mediated emission line width broadening in compounds where Mn­(II) ions exhibit both octahedral and tetrahedral coordination. Furthermore, our previous research has demonstrated analogous temperature-dependent emission behavior, leading to STE emission. , However, it is important to note that not all low-dimensional manganese hybrid halides exhibit similar temperature-dependent behavior . High polyhedral distortion plays a pivotal role in the resulting electron–phonon coupling-mediated STE emission.…”
Section: Introductionmentioning
confidence: 99%
“…STEs are transient defect species that emerge as a consequence of elastic lattice distortion by photoexcitation in a soft deformable lattice. Upon photoexcitation, free excitons are generated, which undergo self-trapping quickly due to the elastic lattice distortion stabilized by electron–phonon coupling in a low-dimensional compound with a soft liquid-like crystalline lattice. , Owing to the exciton self-trapping, the compound exhibits large Stokes shift, broad emission spectra, and long luminescence lifetime and is conducive for designing single-component white light LEDs. , Previously, several studies have demonstrated STE emission in hybrid manganese halides featuring Mn­(II) ions in tetrahedral coordination, showcasing red-emitting STE bands. Additionally, other reports have shown electron–phonon coupling mediated emission line width broadening in compounds where Mn­(II) ions exhibit both octahedral and tetrahedral coordination. Furthermore, our previous research has demonstrated analogous temperature-dependent emission behavior, leading to STE emission. , However, it is important to note that not all low-dimensional manganese hybrid halides exhibit similar temperature-dependent behavior . High polyhedral distortion plays a pivotal role in the resulting electron–phonon coupling-mediated STE emission.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhang et al studied the proton transfer processes of the five‐membered (HQ) and six‐membered (HBQ) ring hydroxyquinoline hydrogen bond systems. The result indicates that the change of molecular structure will affect the strength of the intramolecular hydrogen bond and thus affect the proton transfer process to a certain extent [44]. The excited‐state intramolecular proton transfer (ESIPT) reactions of 10‐hydroxybenzoquinoline (HBQ) in different solvents were studied in detail.…”
Section: Introductionmentioning
confidence: 99%